Development of Quantum Teaching-Based Shorof Materials at Madrasah Aliyah - Wasilah Wasilah; Jumhur Jumhur; Raziqa Diah Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is motivated by the problems of students who find it difficult and feel bored in understanding learning, which is caused by the use of monotonous methods and the high language of the book used. This study aims to develop quantum teaching-based Shorof material to increase student learning effectiveness and determine how students respond to this teaching material. This study uses the Borg and Gall research and development (RD) design model with six steps, namely 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, and 6) product trial. This teaching material product was validated by material experts and media experts and responded to by 11 Putri Azzahro Islamic Boarding School students. The results of the development of this textbook were based on the results of the textbook needs questionnaire with an average percentage of 88.44%, with valid criteria, the results of the material test expert reached a validity level of 92.5% and the results of media experts with a validity level of 86.66% . While the application in class, the pretest results of students get an average score of 38.18% and posttest with an average score of 74.54%. Thus the development of quantum teaching-based Shorof material developed is very feasible to be used to improve students' Shorof learning abilities.